2010
DOI: 10.1007/s11104-010-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

The Rengen Grassland Experiment: relationship between soil and biomass chemical properties, amount of elements applied, and their uptake

Abstract: The Rengen Grassland Experiment (RGE) was established in the Eifel Mountains (Germany) on a low productive Nardetum in 1941. Since then, the following fertilizer treatments have been applied with a late two-cut system: unfertilized control, Ca, CaN, CaNP, CaNPKCl and CaNPK 2 SO 4 . We aimed to understand how concentrations of macro (N, P, K, Ca and Mg), micro (Cu, Fe, Mn and Zn) and trace (As, Cd, Cr, Ni and Pb) elements in the plant biomass were affected by long-term fertilizer application, soil chemical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 74 publications
7
42
4
5
Order By: Relevance
“…Therefore, on the basis of our results it is not possible to declare that the described seasonal patterns of forage quality are typical for these vegetation units in general. But Hejcman et al (2010c) recently reported from a long-term fertilization experiment that late cutting management decreases forage quality more in highly productive (Arrhenatherion elatioris) than in low productive (Violion caninae) plant communities and this is consistent with our results.…”
Section: Forage Qualitysupporting
confidence: 93%
“…Therefore, on the basis of our results it is not possible to declare that the described seasonal patterns of forage quality are typical for these vegetation units in general. But Hejcman et al (2010c) recently reported from a long-term fertilization experiment that late cutting management decreases forage quality more in highly productive (Arrhenatherion elatioris) than in low productive (Violion caninae) plant communities and this is consistent with our results.…”
Section: Forage Qualitysupporting
confidence: 93%
“…For all nutrients, we found a significant decline from April to July. Decreasing nutrient concentrations during the growing season are a well-known phenomenon and could be traced back to ongoing senescence of plant tissues, changes in the leaf:stem ratio, nutrient allocation to roots and losses of, e.g., nutrient-rich seed biomass (Bobbink et al 1989;Marschner 2005;Hejcman et al 2010b;Mládek et al 2011). Reduced growth of young nutrient-rich plant tissues because of summer drought may also be a relevant factor (Kahlert et al 2005).…”
Section: Effects Of Abiotic Site Conditions and Seasonality On Biomasmentioning
confidence: 99%
“…Due to the low N fertilizer levels, the species that were developed for relatively intensive management conditions such as Festulolium had an extremely low CP content. This can be an effect of senescence and retranslocation of N into storage organs (Hejcman et al 2010). Archer and Decker (1977) determined that the CP content in Festuca arundinacea was lower compared to Dactylis glomerata in the autumn.…”
Section: Discussionmentioning
confidence: 99%